The Queen's obligation & inter-governmental committee report - Zainnal Ajamain (Formation of Malaysia series., 2015)
"The Queen's obligation & Inter-Governmental Committee report is the second part of the Formation of Malaysia Series and is an attempt to make sense of the formation of Malaysia from a Sabah's perspective.The British in the Borneo territories empathized with the people in the Borneo, they were not the Colonialist or imperialist that political rhetoric and polemic tend to label them. They were in Borneo to protect the people rather than to exploit them; Sukarno's warning that Malaysia is just a transfer of power from London to Kuala Lumpur was not far off the mark. This narrative acknowledges the role that the people from Baram in Sarawak who petition Her Majesty the Queen of England to remind her of the Queen's Obligation towards the Sarawak Constitution and the 9 Cardinal Principles of the White Rajah..."--Back cover.